New structural insights into the decoding mechanism: Translation infidelity via a G·U pair with Watson–Crick geometry. Issue 13 (23rd May 2013) - Demeshkina, Natalia; Jenner, Lasse; Westhof, Eric; Yusupov, Marat; Yusupova, Gulnara
Abstract : Pioneer crystallographic studies of the isolated 30S ribosomal subunit provided the first structural insights into the decoding process. Recently, new crystallographic data on full 70S ribosomes with mRNA and tRNAs have shown that the formation of the tight decoding centre is ensured by conformational rearrangement of the 30S subunit (domain closure), which is identical for cognate or near‐cognate tRNA. When a G·U forms at the first or second codon–anticodon positions (near‐cognate tRNA), the ribosomal decoding centre forces the adoption of Watson–Crick G·C‐like geometry rather than that of the expected Watson–Crick wobble pair. Energy expenditure for rarely occuring tautomeric base required for Watson–Crick G·C‐like G·U pair or the repulsion energy due to steric clash within the mismatched base pair could constitute the only cause for efficient rejection of a near‐cognate tRNA. Our data suggest that "geometrical mimicry" can explain how wrong aminoacyl‐tRNAs with G·U pairs in the codon–anticodon helix forming base pairs with Watson–Crick geometry in the decoding center can be incorporated into the polypeptide chain.